Integration of Smart Rainwater Harvesting and Islamic Ecological Ethics: IoT-Based Community Empowerment in a Coastal Area of Demak - Jenny Putri Hapsari; Mila Karmilah; Muna Yastuti Madrah; Candra Setiawan; Zaky Naufal; Anis Lailatul Fitriyah; Jeni Nurchasanah; Dewi Ilma Mustafidah; Ahmad Najib Mafaza; Andi Kukuh Agusta (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
The northern coastal area of Demak, particularly Timbulsloko Hamlet, faces a severe clean water crisis due to tidal flooding, seawater intrusion, and land subsidence. Conventional rainwater harvesting (RWH) efforts initiated by local residents have been unable to sustainably meet household needs because of limited capacity and the absence of adequate filtration systems. This community service program aims to develop an IoT-based Smart Rainwater Harvesting (Smart-RWH) system as an adaptive, affordable, and community-driven solution. The implementation methods included community outreach, training on RWH management and maintenance, installation of a Smart-RWH system equipped with water quality sensors, and trial use of a simple Android-based monitoring application. The results indicate the successful installation of a 6,000-litre Smart-RWH unit with pH and volume sensors, the development of an operational manual, and improved community capacity in managing clean water using technology. The implications extend beyond increased access to safe water, as the program also strengthens socio-ecological resilience through local institutional empowerment and collective action. The Smart-RWH model offers significant potential for replication in other coastal areas facing similar challenges.